Agro-economic evaluation of a pineapple production system - Reinhardt, Domingo Haroldo R. C. (Pesquisa Agropecuaria Brasileira, 2014)
Recommendations from a pineapple production system were tested in two experiments. An agro-economic evaluation of the experiments Showed that the current production system, if well plied, would lead to good productivity and satisfactory economic reward, although new techniques including mechanization could reduce the production costs and increase the profits. It is recommended a review of the actual control methods of the pineapple fruit borer (Thecla basilides).